A formação ética do psicólogo ambiente acadêmico e competência moral - Bereta, Thaísa Angélica Déo da Silva (Editora Oficina Universitária, 2020)
This work addresses the problem of training in Psychology, especially regarding ethical and moral training for the exercise of the profession. It presents concepts, curricular guidelines, interdisciplinarity, active methodologies and the role of the teacher; collaborating with the reflection of undergraduate students in Psychology and Education, teachers, educational institutions and class councils concerned with the ethical formation of Psychology in Brazil. When approaching the ethical training of psychologists, we have a view of the dimensions assumed by this scientific knowledge, whether in the relationship with oneself, whether in interpersonal relationships, whether in the political position with society or, even, in the possibility of building a critical conception of the environment. In the teaching-learning process, supervised internships in Psychology enable the formation of professionals with greater capacity for integration between theory, technique and practice. This integration contributes to greater sensitivity of professionals to the demands, to the integrality of the other and to their social and ethical role.